Khalwat Non-Muslim Dalam Qonun Jinayat di Aceh: Diskursus Syariat Islam dan Hak Asasi Manusia - Muhammad Yunus Hidayatullah; Nur Rohmah; Al-Hallaj , Kenneth Sulthon Alafi; Riyadi, Abdul Kadir (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2025)
In this article, we examine the application of Aceh Qanun No. 6/2014 on the law of jinayat against acts of khalwat committed by non-Muslims. The aim of the research is to analyse the legal provisions for non-Muslims who commit acts of khalwat based on the provisions of the Qanun Jinayat. This type of research is normative jurisprudence. It uses a deductive approach. The sources of data chosen will be both primary and secondary data. The primary source of data is the Aceh Qanun No. 6/2014 on the Jinayat Law. Meanwhile, the secondary sources of data consist of various books, articles, magazines, and various pieces of information related to the Khalwat movement in Aceh. The result of this research is that non-Muslims who engage in khulwat, whether with Muslims or not, are subject to the applicable provisions of Qanun Aceh No. 6/2014 and do not need to be given the freedom to choose whether to be tried under the Qanun Jinayat or the national law (KUHP). Khalwat crimes are not specifically regulated by the national law (KUHP). The punishment for non-Muslims who commit khalwat is uqubat ta'zir caning up to 10 times or paying a fine of up to 100 grams of pure gold or imprisonment for up to 10 months. With the application of Islamic law to non-Muslims who violate the laws of jarimah, the provisions of which are not regulated in the National Law (KUHP), the Aceh Qanun will continue to cause controversy both nationally and internationally.